Electronic properties of [111] hydrogen passivated Ge nanowires with surface substitutional lithium. Issue 1 (May 2020) - Arellano, L G; Salazar, F; Trejo Baños, A; Miranda, A; Pérez, L A; Cruz-Irisson, M
Abstract: In this work, a density functional theory study of the lithium (Li) effects on the properties of hydrogenated germanium nanowires (H-GeNWs) is developed. In particular, the electronic band structures, densities of states, formation energies, and Li binding energies of H-GeNWs grown along the [111] crystallographic direction with a diamond structure for different concentrations of surface substitutional Li atoms were studied. Ge nanowires with hexagonal cross sections and three different diameters were considered. The results indicate that all studied H-GeNWs maintain a semiconducting behaviour and the size of the energy band gap is a function of the diameter and the concentration of substitutional surface Li atoms. The formation energy analysis reveals than the energy stability of the nanowires increases when the nanowire diameter and the concentration of Li atoms augment. The results of this work give insight of how the electronic properties of H-GeNWs change during the charging process and open the possibility to incorporate them as electrodes in Li-ion batteries.